The execution of court’s decisions in the new Procedural Labor Act - Ayvar Roldán, Carolina (2020)
In this essay we analyze the consequences of the new procedural labor Act and its application to the final stage of the judicial process specially. In other words, we analyzed the execution of court’s decision and the settlement agreement of the judicial conciliation, because this legal instrument proves the importance of the effectiveness of the judicial process. Furthermore, this two elements serve to value the resonance of the citizen’s claim and the recognition of their civil rights.